What is the impact of the web on local journalism? Two case studies in Toulouse, France. - Bousquet, Franck; Smyrnaios, Nikos; Bertelli, Dominique (Brazilian journalism research, 2014)
Our article aims to explore how the emergence of independent journalism could reconfigure local news. Our field research, carried out from January to April 2013, focuses on two news-based websites in Toulouse: Carré d'infos and LibéToulouse. The results of our research show how newcomers to the world of independent journalism are struggling to maintain their business. A business which is even more precarious than that of their national counterparts, also highlighting the low number of readers and limited exposure they get within the local public space. However, our study has shown that these new players concentrate on field reporting, covering issues that mainstream media often does not and, in particular, cherishing their independence from local politics and economics.